The Effect of Workplace Empowerment, Quality of Work-Life, Work-Life Balance, Organizational Citizenship Behavior on Job Satisfaction - Bagus Caesar Sukmayuda; Unggul Kustiawan (HK-Publishing, 2022)
AbstactThis study aims at discovering how much the effect of work empowerment, quality of work-life, work-life balance, organizational citizenship behavior on job satisfaction of workers in manufacturing being continuing their education in Banten Province, Indonesia. For the respondents, they were workers being continuing their education as many as 230 respondents, they were selected by employing a purpose sampling method, they are students having been actively working in manufactire for more than two year of Banten province, Indonesia, this study is a quantitative research employing factor analysis and structural equation modeling (SEM) with Lisrel.The findings of this study are work empowerment, quality of work-life, work-life balance, organizational citizenship behavior can increase job satisfaction. The managerial implication of the study is that by increasing and paying attention to organizational citizenship behavior carried out by the company, there will be a satisfaction in work; and the employee will fully encourage the function of the organization. This study is expected to contribute in providing information at the theoretical/scientific level of human resource management and the company's strategy in noticing the level of positive employee job satisfaction. Especially, it is for employees working while continuing their education in increasing job satisfaction.Keywords: Workplace Empowerment, Quality of work-life, Work-Life Balance, Organizational Citizenship Behavior, Job Satisfaction. AbstrakPenelitian ini bertujuan untuk mengetahui seberapa besar pengaruh pemberdayaan kerja, kualitas kehidupan kerja, keseimbangan kehidupan kerja, perilaku kewargaan organisasional terhadap kepuasan kerja pekerja manufaktur yang melanjutkan pendidikan di Provinsi Banten, Indonesia. Untuk responden merupakan pekerja yang sedang melanjutkan pendidikan sebanyak 230 responden, dipilih dengan metode purposive sampling yaitu mahasiswa yang telah aktif bekerja di bidang manufaktur lebih dari dua tahun di Provinsi Banten, Indonesia. penelitian kuantitatif menggunakan analisis faktor dan structural equation modeling (SEM) dengan Lisrel. Temuan penelitian ini adalah pemberdayaan kerja, kualitas kehidupan kerja, keseimbangan kehidupan kerja, perilaku kewargaan organisasi dapat meningkatkan kepuasan kerja. Implikasi manajerial dari penelitian ini adalah dengan meningkatkan dan memperhatikan perilaku kewargaan organisasi yang dilakukan oleh perusahaan maka akan timbul kepuasan dalam bekerja; dan karyawan akan sepenuhnya mendorong fungsi organisasi Penelitian ini diharapkan dapat memberikan kontribusi dalam memberikan informasi pada tataran teoritis/ilmiah manajemen sumber daya manusia dan strategi perusahaan dalam memperhatikan tingkat kepuasan kerja pegawai yang positif. Khususnya bagi karyawan yang bekerja sambil melanjutkan pendidikan dalam meningkatkan kepuasan kerja.Katakunci: Permberdayaan kerja, Kualitas kehidupan kerja, Keseimbangan Kehidupan Kerja, Perilaku Kewarganegaraan Organisasi, Kepuasan Kerja.